2021
DOI: 10.1088/1361-6463/abfad3
|View full text |Cite
|
Sign up to set email alerts
|

Graded magnetic materials

Abstract: Graded magnetic materials represent a promising new avenue in modern material science from both fundamental and application points of view. Over the course of the last few years, remarkable results have been obtained in (epitaxial) heterostructures based on thin alloy films featuring diverse compositional depth profiles. As a result of the precise tailoring of such profiles, the exchange coupling, and the corresponding effective or local Curie temperatures can be controlled over tens of nm with an excellent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 174 publications
0
13
0
2
Order By: Relevance
“…Each sample has a well-defined global Curie temperature, where the remanence is reduced to zero, but, nonetheless, we can define a local Curie temperature that can be higher or lower, depending on the local concentration of the magnetic element. [32][33][34] At the global Tc, there may still exist disconnected regions that are magnetically ordered, but they do not exhibit long range ordering in the absence of an external field. These are essentially superparamagnetic regions that are easily polarizable and can mediate exchange coupling and proximity effects over several tens of nanometers.…”
Section: Composition Distributionmentioning
confidence: 99%
“…Each sample has a well-defined global Curie temperature, where the remanence is reduced to zero, but, nonetheless, we can define a local Curie temperature that can be higher or lower, depending on the local concentration of the magnetic element. [32][33][34] At the global Tc, there may still exist disconnected regions that are magnetically ordered, but they do not exhibit long range ordering in the absence of an external field. These are essentially superparamagnetic regions that are easily polarizable and can mediate exchange coupling and proximity effects over several tens of nanometers.…”
Section: Composition Distributionmentioning
confidence: 99%
“…B. J. Kirby and L. Fallarino et al also reported the fabrication of exchange strength modulated ferromagnetic alloy films of Co 1− x Ru x in which the up- and down-graded composition sequence was repeated on a nanometer scale. 43 A recent review by this group 44 would be helpful for more details on magnetic metal alloy NCGCs.…”
Section: Design Of Functionalities In Ncgm Filmsmentioning
confidence: 99%
“…В последние несколько лет в зарубежной литературе, посвященной исследованию магнитных материалов и сплавов, можно встретить термин " Graded Magnetic Materials" или градиентные магнитные материалы (ГММ), это материалы, которые проявляют пространственно-зависящие магнитные свойства (см., например, обзор [1] и ссылки в нем, а также работу [2]). ГММ привлекают внимание исследователей как с фундаментальной, так и с прикладной точек зрения, потому что путем подбора профилей распределения состава по глубине становится возможным контролировать обменное взаимодействие и соответствующие эффективные или локальные температуры Кюри на масштабах нескольких нанометров [1,3,4].…”
Section: Introductionunclassified